Effect of pressure pulse on geomagnetic field oscillations - Sinha, Ashwini K.; Rajaram, R. (My University, 2006)
The effect of solar wind pressure pulse on geomagnetic field oscillations has been computed by using Green’s function technique. The dominance of toroidal oscillations during dawn/dusk sectors appears to be natural consequences of solar wind pressure pulse and may not be attributed to K-H instability at the magnetopause boundary caused by velocity shear. Pressure pulse generates surface waves at the magnetopause boundary and couples to the field oscillations to give rise such effects. The paper adopts the 3-dimensional approach to explain the phenomena.
Keywords: Field line response; Geomagnetic pulsations; Solar wind impulse; Standing waves; Geomagnetic field